Hubungan antara kualiti hidup dengan kebimbangan dan kemurungan warga emas demensia - Noraini Che’ Sharif,; Khadijah Alavi,; Ponnusamy Subramaniam,; Nurul Erni Nazira Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The quality of life of older adults of dementia is interdependent among the anxiety and depression experienced by older adults of dementia in institution. The aims of this article is to examine the relationship between anxiety and depression with the quality of life of older adults with dementia in the institution and the role of social workers in carrying out meaningful activities at care institutions to enhance the well-being of the older adults. A total of 58 older adults with mild to moderate dementia were selected through a series of screening process by a qualified clinical psychologist. Several instruments has been used including Quality of LifeAD (QoL-AD), Geriatric Depression Scale (GDS), Beck Anxiety Inventory (BAI) to investigate the relationship between anxiety and depression with quality of life among the older adults with dementia. A findings from this study show that there is a negative relationship between the level of anxiety and depression with quality of life among the older adults with dementia. The main implication of this article is that social workers should be trained to conduct meaningful activities to help person with dementia in institutions to reduce anxiety and depression and improve the quality of life.